EFFECT OF CHRONIC KIDNEY FAILURE ON MORPHOLOGICAL INDICATORS OF THE SPLEEN - Sherzod Sh. Sobirov,; Dilnoza A. Khasanova,; Dilshod K. Khudoiberdiev, (Central Asian Journal of Medicine, 2025)
Chronic kidney disease remains a serious public health problem worldwide, not only in terms of medical but also social and economic aspects. In recent years, there has been an increase in kidney disease. Today, the main diseases causing chronic kidney dailure (CKD) are diabetes mellitus, arterial hypertension, chronic glomerulonephritis, as well as a combination of these diseases. It is known that the incidence of chronic kidney disease and kidney failure varies significantly in different regions and remains a serious and pressing health problem. According to statistics, 1.2 million people died from chronic kidney disease worldwide in 2017. From 1990 to 2017, the global mortality rate from cardiovascular diseases among all ages increased by 41.5%, although there were no significant changes in the age-standaedized mortality rate. The global prevalence of CKD among all ages increased by 29.3% during this period.